Customer Domination at Work: A New Paradigm for the Sexual Harassment of Employees by Customers - Albin, Einat (2017)
This Article introduces a novel legal paradigm—customer domination at work—to address the sexual harassment of employees by customers. This new approach challenges the prevailing paradigm, which focuses on the employer-employee binary relationship. I show how, under current Title VII law, the prevailing paradigm leads to a weaker form of employer liability than other instances where employers are liable for the sexual harassment of their employees. The protection for workers is also limited. The same is true of two other legal regimes discussed in the Article: Germany and Britain. More importantly, I argue that the prevailing paradigm precludes a true understanding of the problem of third-party harassment that recognizes the power of customers within an employer- employee-customer triangular relationship, seeing the customer as integral to the organization of work. Within the triangular relationship, customer domination at work is created, consisting of three aspects: masculinity, authority, and service market power. Customer domination is shaped and reinforced by employers, and is exploited by customers in these cases of harassment. This should lead, I claim, to placing stricter legal liability on employers, incentivizing them to change workplace practices that provide customers with such power, and to customers bearing legal responsibility that parallels employer liability